2017
DOI: 10.1108/el-09-2016-0184
|View full text |Cite
|
Sign up to set email alerts
|

Emotion evolutions of sub-topics about popular events on microblogs

Abstract: Purpose The development of social media has led to large numbers of internet users now producing massive amounts of user-generated content (UGC). UGC, which shows users’ opinions about events directly, is valuable for monitoring public opinion. Current researches have focused on analysing topic evolutions in UGC. However, few researches pay attention to emotion evolutions of sub-topics about popular events. Important details about users’ opinions might be missed, as users’ emotions are ignored. This paper aims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Previous research on sentiment analysis in social networks has generated fruitful results using supervised classifier learning [ 19 , 20 , 21 , 22 ] and unsupervised emotion lexicon-based methods [ 23 , 24 ]. Most supervised methods are conducted by extracting linguistic features and constructing classifiers using machine-learning or deep-learning techniques.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on sentiment analysis in social networks has generated fruitful results using supervised classifier learning [ 19 , 20 , 21 , 22 ] and unsupervised emotion lexicon-based methods [ 23 , 24 ]. Most supervised methods are conducted by extracting linguistic features and constructing classifiers using machine-learning or deep-learning techniques.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Reference [ 31 ] found that during the 2007 Virginia Tech shooting, anger was the most frequently expressed emotion on Twitter, followed by fright, sadness, and anxiety. In terms of natural disasters, Reference [ 21 ] collected microblogs about the “H7N9” influenza and classified them into different emotion categories using a supervised classification method. A topic model was then used to extract subtopics about the event.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several works have tried to model both topics and emotion. [36] extracts topics using LDA [2], and the emotion of each microblog is determined using a supervised emotion classifier. The topic-emotion models in [9,16,26,27,35] learn a supervised topicaware emotion classifier.…”
Section: Related Workmentioning
confidence: 99%
“…This disjoint analysis is a limitation of those approaches as meaningful clues hidden in online data are often a combination of topics and subjective aspects and their identification involves analysis of emotions conveyed towards specific topics. To overcome this limitation, several studies addressed the dynamics of emotions or opinions in time [29] as well as detecting the mapping between the emotional categories and linguistic instances [30].…”
Section: A Analysis Of Specific Online Contentsmentioning
confidence: 99%